CTE - Workshop on Cloud Technologies in Education - S. O. Semerikov; A. M. Striuk (Academy of Cognitive and Natural Sciences, 2013)
Today we are presenting the 1st volume of CTE Workshop Proceedings, a Diamond Open Access peer-reviewed journal published annually by the Academy of Cognitive and Natural Sciences. CTE Workshop Proceedings depict the latest achievements in educational technology research - revealing emerging trends and new ideas before they appear in journals. CTE Workshop Proceedings offer broad coverage of new ideas, methodologies, and projects in fast-moving areas of research related to cloud technologies in education.